Pengembangan Bahan Ajar Buku Teks IPS Tema Indahnya Kebersamaan Pada Peserta Didik Kelas 4 MI An Nuriyah Kwanyar Bangkalan - Nurul Makrifah Faqih; Nur Fauzi (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2020)
This research aims to develop Social Science Textbook teaching materials. The material teaching is developed in the form of social studies textbooks with the theme